United States' bankruptcy jurisdiction over foreign entities: exorbitant or congruent - Walters, Adrian J. (The Journal of Corporate Law Studies, 2017)
Alarmed at the ease with which global bankruptcy jurisdiction can be engineered in the US through a combination of the Bankruptcy Code’s low bar to entry and the worldwide effects of a bankruptcy case, critics argue that the US promotes abusive bankruptcy forum shopping and harmful imposition of US norms on overseas stakeholders. This article advances a revised account of US bankruptcy jurisdiction over non-US debtors from a distinctively Anglo-American standpoint. The article’s central thesis is that critics overemphasise formal jurisdictional rules and pay insufficient attention to how US courts actually exercise jurisdiction in practice. It compares the formal law ‘on the books’ in the US and UK for determining whether or not a domestic insolvency or restructuring proceeding relating to a foreign debtor can be maintained in each jurisdiction and provides a functional account of how US bankruptcy jurisdiction over foreign entities is exercised in practice using the concept of jurisdictional congruence as a benchmark.

Creditors' rights in business rescue proceedings in terms of South Africa's Companies Act 71 of 2008 - Rugumamu, Victor William (University of KwaZulu-Natal, 2017)
The focus of this study is the protection of creditors’ rights in South Africa’s statutory business rescue regime provided for in Chapter 6 of the Companies Act 71 of 2008. In this analysis, three issues in particular are addressed in depth. The first is the creditors` power to initiate the business rescue process. The second is the position of creditors between the commencement and the termination of the business rescue process. The third issue is to suggest (on the basis of experience drawn from reported case law and academic criticism of the current business rescue statutory provisions) an improved model that will more effectively safeguard creditors’ rights in South Africa’s business rescue regime. In exploring these issues, I give a critical review of pertinent literature. With respect to the first issue, I conclude that the legislative provisions granting creditors the right to seek a court order initiating the business rescue process are open to criticism. By contrast, a resolution of the board of directors for the commencement of business rescue is a simpler route. With regard to the second issue I conclude that the company’s creditors have considerable influence in the business rescue process. Overall, the current statutory business rescue regime is intended to give a voice to all major stakeholders in the company’s continued solvent existence. In the event of certain irresoluble disputes in the course of that process, the judiciary has the final say. A substantial number of judicial decisions have provided interpretations of the statutory provisions, and the trend has been to try to restore financial ailing companies to solvency and viability where there is a reasonable prospect for success in this regard. In my conclusion, I propose a legislative model that seeks to strike an optimum balance between the competing and sometimes conflicting interests of the various interested parties and I suggest reforms directed at enhancing the protection of creditors’ rights. This thesis takes account of South African legislation and legislative amendments as at 31 December 2016 and of decisions of the South African courts up to and including those handed down during April 2017 and reported in the saflii on-line law reports. Since a substantial part of this thesis was written from outside South Africa, the author relied heavily on the safllii data base of judgments of the South African courts, rather than on hard copy law reports which take time to reach their destination by post.
Keywords: Financial distress; Liquidation; Rationale for business existence